Training on Creating Digital ILAU Based on Local Cultural CharacterBima for Middle MTS Teachers in Bima Regency - Yamin, Muhammad; Rostati, Rostati; Rafiun, Afif; Salahuddin, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The method used was focus group discussion (FGD) and a questionnaire. The aim of conducting an FGD is to seek in-depth information regarding the implementation of the training that has been carried out. Meanwhile, the questionnaire given aims to determine the level of understanding felt by the training participants. The final results will determine the success of the activities that have been carried out. The method for implementing this service activity is UKBM development training based on local cultural characters. At the end of the mentoring activities, an evaluation is carried out to determine the achievements of the implementation of the community partnership program. Implementation achievements can be seen from several indicators: (1) understanding of UKBM (2) skills in creating digital UKBM based on local cultural characteristics (3) ability in developing UKBM, with an increase of more than 60%. From the results of the questionnaire analysis, it can be concluded that there has been an increase in teachers' understanding of the importance of using technology in learning by 52%, an increase in skills in making digital UKBM based on local cultural characters by 55%, and an increase in the ability to make learning tools by 63%. This is in accordance with the goal to be achieved, namely an increase of more than 50%. Apart from that, the team also provided a questionnaire on the level of teacher satisfaction with the implementation of the training. The questionnaire contains 6 closed questions using 4 Likert scales, namely disagree, agree, strongly agree and very much agree. The results of the teacher satisfaction level questionnaire regarding the implementation of the training showed that 75% of teachers agreed that the material was easy to understand, 10% said they strongly agreed, 10% said they strongly agreed, and 5% disagreed. Some teachers are new to and know how to use the Ispring suite. Meanwhile, 80% agreed that they wanted to apply the results of this training to learning, 10% said they strongly agreed, and 10% strongly agreed.